2020
DOI: 10.1055/s-0039-1701076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiO2 Nanoparticles Addition on the Flexural Strength of Repaired Acrylic Denture Base

Abstract: Objective The objective of this study was to evaluate the effect of nano-SiO2 addition on the flexural strength (FS) of repaired acrylic denture base. Materials and Methods Heat-polymerized acrylic resin specimens were fabricated in dimensions of (65 × 10 × 2.5 ± 0.1 mm3 ) and then sectioned and prepared, creating repair gap with butt (90 degrees) and bevel (45 degrees) repair surface designs forming two main groups according to joint design. Further subdivision was done into four groups (n = 10) according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…Therefore, good mechanical properties are required for the functional performance of denture base materials (biofunctionality). Considering the significance of the mechanical properties, several modifications have been reported for various mechanical properties of PMMA, including its flexural strength [ 14 , 30 , 33 , 68 , 134 , 135 , 136 ], impact strength [ 14 , 137 , 138 , 139 , 140 ], fracture toughness [ 141 , 142 , 143 ], and surface hardness [ 67 , 98 , 141 , 144 , 145 ]. The flexural strength (also known as the modulus of rupture or transverse strength) is assessed using a 3-point bending test according to the guidelines of ISO 20795-1 [ 81 ].…”
Section: Properties Of Pmmamentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, good mechanical properties are required for the functional performance of denture base materials (biofunctionality). Considering the significance of the mechanical properties, several modifications have been reported for various mechanical properties of PMMA, including its flexural strength [ 14 , 30 , 33 , 68 , 134 , 135 , 136 ], impact strength [ 14 , 137 , 138 , 139 , 140 ], fracture toughness [ 141 , 142 , 143 ], and surface hardness [ 67 , 98 , 141 , 144 , 145 ]. The flexural strength (also known as the modulus of rupture or transverse strength) is assessed using a 3-point bending test according to the guidelines of ISO 20795-1 [ 81 ].…”
Section: Properties Of Pmmamentioning
confidence: 99%
“…Ideally, the denture base should have a high flexural strength to bear the complex forces of mastication without permanent deformation or fracture [ 9 ]. A number of studies have investigated [ 14 , 30 , 33 , 68 , 134 , 135 , 136 ] flexural strength using various methods and types of PMMA. Barbrosa et al [ 146 ] reported good flexural strength for heat-cured, cold-cured, and microwave-cured PMMA (92.84 ± 4.73, 84.40 ± 1.68, and 109.63 ± 5.31 MPa, respectively).…”
Section: Properties Of Pmmamentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30][31] Soft liners are even more susceptible to plaque accumulation and fungal infection than hard liners and acrylic denture bases. [5][6][7][8] To prolong the clinical longevity of these materials and reduce the possibility of biofilm accumulation, several solutions have been suggested. 1,11,32,33 Researchers have attempted to add antimicrobial and antifungal agents to the composition of liners.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Addition of low concentrations of nano-SiO 2 to acrylic denture base was reported to be a promising method for improving denture longevity and repair strength. 8 The SNPs' incorporation within the acrylic denture base material was even stated to improve its viscoelastic properties. 9 Adequate bonding of soft liners to the acrylic denture bases is essential to ensure their performance.…”
Section: Introductionmentioning
confidence: 99%